Disentangling anthropogenic and dynamic contributions to recent ocean warming - Jiheun Lee; Rémi Tailleux; Till Kuhlbrodt (npj Climate and Atmospheric Science)
Abstract As the ocean absorbs over 90% of excess radiative heat, recent ocean warming is shaped by a combination of anthropogenic surface heat gain and dynamical processes redistributing heat. To distinguish these contributions, we introduce a novel framework that decomposes temperature changes into three components: ‘spice’ (density-compensated variability) and ‘heave’ (density-contributing variability), with heave further divided into ‘passive’ (net warming) and ‘dynamic’ (redistribution) contributions. Passive heave captures anthropogenic warming subducted along isopycnals, while spice and dynamic heave, which globally sum to zero, represent heat redistribution. Observations and climate models demonstrate general agreement on passive heave, establishing it as a key oceanic fingerprint of anthropogenic climate change. In contrast, dynamic heave, driven by interannual-to-decadal variability, exhibits significant spatial heterogeneity, with notable discrepancies between models and observations. This framework links ocean heat uptake to sea-level change, with passive heave driving global thermosteric rise and dynamic heave contributing to regional dynamic sea level changes.